DIGITAL LITERACY COMPETENCE: ANALYSIS OF ELEMENTARY SCHOOL STUDENTS’ FAMILY RESOURCE MANAGEMENT IN LEARNING (QUANTITATIVE METHOD IN NGAWI) - Tri Wahyuni Maduretno; Wiwik Angelita Sari; Siti Ulfatur Rosidah; Fatma Anggraini (Universitas Bhinneka PGRI, 2026)
Digital literacy is the ability to read and write digitally. The need for parents become a facilitator learning at home with technological support to their children. Initial data from several schools in Ngawi, Indonesia, showed that the school provided socialization to parents for the provision of technological facilities for learning at home. Purpose of research was to analysis the management of family resources for digital literacy of elementary school students in learning. This research used a quantitative approach. The population was 374 students (SDN Jambangan I and IV, SD IT Al Kiram Jambangan). Sampling technique was simple random sampling. This sample was 193 students. Data collection technique was a questionnaire with indicators, namely planning, organizing, implementing, controlling families regarding students' digital literacy. Data analysis technique used quantitative descriptive. The results were the role of the family in the scope of family resource management towards digital literacy of elementary school students with a planning percentage of 69.5%, organizing 76.4%, implementing 88.4%, controlling 94.5%. Therefore, managing the abilities of family members is important in helping students develop digital literacy skill in learning.